Pre-Service Teachers’ Voices: The Challenges in Dealing Classroom Management Problems During Teaching Practice - Ninda Maulidina; Maisa Maisa; Diana Rahmawati Rozak (Linguistics and ELT Journal, 2022)
This study focuses on the classroom management problems of pre-service teachers during teaching practice and how they apply teaching strategies to overcome those problems. The method used is a qualitative narrative inquiry with data sources that have been collected through a questionnaire, documents evidence and interviews. Data analysis for this study used thematic analysis. The results of the analysis found that classroom management problems are one of the difficulties and challenges for pre-service teachers. The setting of strategies in lesson planning and managing in the classroom is really needs to be considered by pre-service teachers to achieve the learning goals. Efforts that can be made with the help of using pre-service teachers when facing classroom management problems are designing the teaching strategies and pre-service teachers need to provide motivation, instruction and pay attention to student behavior.